2019
DOI: 10.1016/j.atmosenv.2019.04.050
|View full text |Cite
|
Sign up to set email alerts
|

Impact of emission controls on air quality in Beijing during APEC 2014: Implications from water-soluble ions and carbonaceous aerosol in PM2.5 and their precursors

Abstract: Impact of emission controls on air quality in Beijing during APEC 2014: implications from water-soluble ions and carbonaceous aerosol in PM 2.5 and their precursors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(31 citation statements)
references
References 90 publications
3
27
0
1
Order By: Relevance
“…The total ions summed to 24.3±4.9% (Lab-4) to 33.8±7.1% (Lab-1) of PM2.5. These results are comparable with those in another study in Beijing which found that SNA accounted for 88% of total ions and 9-70% of PM2.5 concentrations (Xu et al, 2019b). As shown in Table 2, the recoveries of most ions measured by Lab-4 were < 100%, while those of Lab-1 were much higher, especially for major ions (>100%).…”
Section: Detection Limitssupporting
confidence: 88%
“…The total ions summed to 24.3±4.9% (Lab-4) to 33.8±7.1% (Lab-1) of PM2.5. These results are comparable with those in another study in Beijing which found that SNA accounted for 88% of total ions and 9-70% of PM2.5 concentrations (Xu et al, 2019b). As shown in Table 2, the recoveries of most ions measured by Lab-4 were < 100%, while those of Lab-1 were much higher, especially for major ions (>100%).…”
Section: Detection Limitssupporting
confidence: 88%
“…Besides, secondary organic aerosol (SOA) formed from the oxidation of volatile organic compounds ( Seinfeld and Pandis, 2006 ) is also an important component of PM 2.5 in China ( Huang et al, 2014 ; Zhao et al, 2016 ). The concentration, composition and properties of SOA showed complicated responses to the emissions of NO x and VOC s ( Feng et al, 2019 ; Tsimpidi et al, 2008 ; Xu et al, 2019 ). However, the simulation of SOA is usually seriously underestimated by more than tenfold in China because of the poor understanding of its precursors, chemical mechanisms and physicochemical characterization ( Jiang et al, 2012 ; Li et al, 2011 ; Robinson et al, 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that NH 4 + concentrations measured in this study were relatively low compared with those in other areas ( Table 2). One possible explanation is that NH 3 volatilization from soil is limited by low temperature at the altitude of 4000 m. SO 4 2and NO 3 mainly come from oxidation of sulfur dioxide and nitrogen oxides, emitted by a wide range of anthropogenic sources, such as coal and fuel combustion Xu et al, 2019b). High concentrations of SO 4…”
Section: Fog and Rain Chemistry Characterizationmentioning
confidence: 99%